Writing Summary as An Alternative Strategy To Comprehend The Text - Dian Permatasari Sucita; Salmon James Hukom (MATAI: International Journal of Language Education, 2022)
This paper is purposed to explain the use of Writing Summary as an alternative strategy to comprehend the text in teaching reading. Some researchers have applied writing the summary strategy to increase students' reading comprehension. Based on the results of those researches, showed that writing summary could effectively encourage students in comprehending the text well. Writing summary can help students enhance understanding of what is read. The strategy requires that students rewrite or outline only the important parts of the passage. Writing summary encourages students look for the most important parts and determine what parts of a passage are less important and what should be ignore. By using this strategy, the students need to read the whole text in order to make a summary using their own words. So, by writing summary based on what they read, they can comprehend a passage.